Jacksonville, Florida, Transportation Authority's Mobility Corridors: Improving Transit System Performance Through Enhanced Safety and Urban Design. Issue 1 (2017) - Jones, Frederick; Sloboden, Jaimison
The Jacksonville Transportation Authority (JTA) is an agency responsible for transit operations and roadway development in Jacksonville (Duval County), Florida. With this responsibility, JTA is uniquely positioned to develop and to implement roadway improvements that directly facilitate transit system access and operations. Since 2012, the commitment to improving transit and safety in the city of Jacksonville has been significant. In December 2014, JTA completed a route optimization initiative that was designed to increase frequency and reliability within a newly defined system of 14 high-frequency mobility corridors. To improve greatly the safety and the experience of the first- and last-mile transit user, JTA created two supporting initiatives as part of the mobility corridors program: transit enhancements and complete streets. These initiatives were intended to deal directly with deficiencies in roadway and transit infrastructure, such as gaps in sidewalks and Americans with Disabilities Act–compliant stops and shelters (transit enhancements initiative). More significantly, they were designed to improve the safety and accessibility for all users of the transit system (complete streets initiative). The focus of this paper is the complete streets initiative that directly targets substantial first- and last-mile challenges via a range of multimodal design strategies and safety countermeasures while establishing a prioritization process for implementation.